Proceedings of National Aerospace and Electronics Conference (NAECON'94)
DOI: 10.1109/naecon.1994.332858
|View full text |Cite
|
Sign up to set email alerts
|

Two robust homing missile guidance laws based on sliding mode control theory

Abstract: Two new guidance laws for short range homing titissiles are developed by invoking the Sliding Mode Control (SMC) theory. Guidance law 1 is structured around the basic Proportional Navigation (PN), with an additive switching term, which is a function of the Line of ,Sight (LOS) rate alone. A n adaptive procedure is suggested to select the gain of the switching term, in order to reduce chattering. This guidance law is nearly as siinple to implement as the P N itself and does not require any explicit target maneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Letĥ denote an estimate of h which can be obtained by following the procedure for IDC-based estimation of the uncertainty given in [23](17) or in the time domain as…”
Section: B Smc and Idc-based Guidance Lawmentioning
confidence: 99%
See 2 more Smart Citations
“…Letĥ denote an estimate of h which can be obtained by following the procedure for IDC-based estimation of the uncertainty given in [23](17) or in the time domain as…”
Section: B Smc and Idc-based Guidance Lawmentioning
confidence: 99%
“…From (8) and (31) and using (17) it can be shown that the last two terms of (34) consist of an estimate of target acceleration. In fact these terms would have given the estimate of target acceleration only had the uncertainty to be estimated (8) been defined in terms of the target acceleration alone.…”
Section: Comparison With Other Guidance Lawsmentioning
confidence: 99%
See 1 more Smart Citation
“…In (Hu et al, 2011), a three-dimensional guidance law has been developed for impact angle control, using the linear quadratic optimal theory and the SMC methodology. Babu et al (1994) developed two guidance laws in twodimensional space for short-range homing missiles by invoking SMC theory and based on PNG. They have also chosen the line-of-sight (LOS) angle rate as the switching surface.…”
Section: Introductionmentioning
confidence: 99%
“…Babu et al (1994) developed two guidance laws in two-dimensional space for short-range homing missiles by invoking SMC theory and based on PNG. They have also chosen the line-of-sight (LOS) angle rate as the switching surface.…”
Section: Introductionmentioning
confidence: 99%